Studie nákupního procesu se zaměřením na řízení zásob - Nedvěd, Jan (Vysoké učení technické v Brně. Fakulta podnikatelská, 2020)
Tato diplomová práce je zaměřena na analýzu současného řízení nákupní činnosti a zásob vzhledem k výrobnímu procesu ve společnosti ŽĎAS, a.s. Na základě provedených analýz práce následně navrhuje konkrétní řešení pro zefektivnění stávajících dílčích procesů.

The diploma thesis focuses on the analysis of the current management of the purchasing process and inventory management for the production process in the company ZDAS, a.s. Based on the performed analyzes, this thesis proposes specific solutions for improving the actual partial processes.
Purchasing Process Study Focused on Inventory Management
Keywords: nákupní proces; řízení zásob; logistika; purchasing process; inventory management; logistics